Програмна система розпізнавання обличчя в системах ідентифікації особистості smart city - Лобенко, Д. М. (ХНУРЕ, 2021)
The purpose of this paper is to review and analyze the main approaches and algorithms used in existing Smart City systems, their advantages and disadvantages, to offer more complete functionality for these systems, including identification systems.
Науковий керівник – к.т.н, доц. каф. ПІ Чуприна А.С.
Keywords: програмна система; ідентифікації особистості